2022
DOI: 10.1007/s10615-022-00838-y
|View full text |Cite
|
Sign up to set email alerts
|

Examining diagnosis as a component of Social Workers’ scope of practice: a scoping review

Abstract: Our study reports on a scoping review examining the role of diagnosis within social work practice in Canada and the United States (US). Adopting the process laid out by Arksey and O’Malley, the search captured 189 academic and grey literature drawn from six health and social sciences databases and published from January 1980 to April 2020. The majority of literature were based in the US, and studies covered a variety of practice settings including hospitals, community clinics, medical health clinics, and priva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…A recent scoping review on diagnosis in clinical social work practice found that there is a need to strengthen social work education and training in diagnosis. At present, there is limited guidance on how to increase competence in social workers to be able to include diagnosis in social workers’ scope of practice (Sur et al, 2022). Table 1 shows which provinces include diagnosis in social workers’ scope of practice.…”
Section: Diagnosismentioning
confidence: 99%
“…A recent scoping review on diagnosis in clinical social work practice found that there is a need to strengthen social work education and training in diagnosis. At present, there is limited guidance on how to increase competence in social workers to be able to include diagnosis in social workers’ scope of practice (Sur et al, 2022). Table 1 shows which provinces include diagnosis in social workers’ scope of practice.…”
Section: Diagnosismentioning
confidence: 99%